(untitled) (Journal of the College of Basic Education, 2022)
This research aims to know the effect of the DSLM-based learning model on the scientific thinking for fourth-grade students in biology by verifying the validity of the following hypothesis. (There is no statistically significant difference at the level of significance (0.05) between the average scores of the experimental group students who study according to the DSLM model based on dual situations learning and the average scores of the control group who study according to the usual method in the scientific thinking test) The researcher adopted the experimental design with partial control for the experimental and control groups, and it represents the research community, which is the fourth-grade scientific students in the preparatory day schools for girls in the Babil Governorate for the academic year (2021-2022). An experimental group whose number of students reached (34) and a control group whose number of students reached (36) students. The equivalence between the students of the two research groups was conducted with the following variables: (pre-information for biology, previous achievement of science for the second grade, intelligence, test of scientific thinking) in the classroom. The first academic year (2021-2022). After completing the experiment, applying the scientific thinking test and obtaining the results, the data were treated statistically using the t-test for two independent samples, and the following results were reached: (The experimental group that studied with the dual situational learning model DSLM) outperformed the control group that studied in the usual way in the achievement test), so the researcher recommends some recommendations and suggestions.